2022
DOI: 10.1108/rbf-11-2021-0256
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural finance and cryptocurrencies

Abstract: PurposeThe present study sets out to examine the empirical literature on the behavioural aspects of cryptocurrencies, showing the findings of related studies and discussing the various results. A systematic literature review of cryptocurrencies in behavioural finance seems to be timely and particularly important in terms of providing a guide for future research. Key topics include an extent review on the issue of herding behaviour amongst cryptocurrencies, momentum effects and overreaction, contagion effect, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…Finally, while cryptocurrencies can be marketed as novel yet attractive products, their current elevated prices suggest little further profit potential for new investors. Additionally, a number of elevated risks similar to online gambling and the seedier side of conventional investments have been found, including market manipulation and scams (Leinweber and Madhavan 2001;FCA 2022;Eigelshoven et al 2021;Kamps and Kleinberg 2018;Mirtaheri et al 2019;Martineau 2018) which can appear attractive via the distorted lens of social media (Benaim 2018;Tandon et al 2021;Shiller 2016;Umar et al 2021;Kumar 2021;Ballis and Verousis 2022;Gorse 2017, 2018;Chen et al 2017;Serafini et al 2020;Hao et al 2019;Garcia and Schweitzer 2015). The lack of regulatory protections in cryptocurrencies adds further support to this narrative of increased risks for many users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while cryptocurrencies can be marketed as novel yet attractive products, their current elevated prices suggest little further profit potential for new investors. Additionally, a number of elevated risks similar to online gambling and the seedier side of conventional investments have been found, including market manipulation and scams (Leinweber and Madhavan 2001;FCA 2022;Eigelshoven et al 2021;Kamps and Kleinberg 2018;Mirtaheri et al 2019;Martineau 2018) which can appear attractive via the distorted lens of social media (Benaim 2018;Tandon et al 2021;Shiller 2016;Umar et al 2021;Kumar 2021;Ballis and Verousis 2022;Gorse 2017, 2018;Chen et al 2017;Serafini et al 2020;Hao et al 2019;Garcia and Schweitzer 2015). The lack of regulatory protections in cryptocurrencies adds further support to this narrative of increased risks for many users.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that herding behaviour is not only present in the cryptocurrency market, but it is also most pronounced during periods of uncertainty (Ballis and Verousis 2022). The role of social media in predicting cryptocurrency bubbles and prices has been widely researched, with Twitter being the platform investigated by most studies.…”
Section: Social Media and Herd Behaviourmentioning
confidence: 99%
“…The results contribute to introduce exchange inflows as an important and new proxy for crypto investor behaviors that, in addition to existing behaviors like herding (e.g. Ballis and Verousis, 2022;Bouri et al, 2019;Evrim Mandaci and Cagli, 2022;Gurdgiev and O'Loughlin, 2020;Shrotryia and Kalra, 2022) and sentiments (e.g. Ballis and Verousis, 2022;L opez-Cabarcos et al, 2021), are impactful to the cryptocurrency market.…”
Section: Introductionmentioning
confidence: 89%
“…Ballis and Verousis, 2022; Bouri et al ., 2019; Evrim Mandaci and Cagli, 2022; Gurdgiev and O’Loughlin, 2020; Shrotryia and Kalra, 2022) and sentiments (e.g. Ballis and Verousis, 2022; López-Cabarcos et al ., 2021), are impactful to the cryptocurrency market.…”
Section: Introductionmentioning
confidence: 99%
“…Bagus and Horra (2021) undertook an ethical assessment of cryptocurrencies, highlighting considerations associated with investment decisions. Insights from the behavioral finance literature aid in understanding investors' psychological factors and decision-making in cryptocurrency investments (Ballis and Verousis 2022;Zhao and Zhang 2021;Choi and Feinberg 2022).…”
Section: Literature Reviewmentioning
confidence: 99%